2004
DOI: 10.1242/dev.00929
|View full text |Cite
|
Sign up to set email alerts
|

Flow regulates arterial-venous differentiation in the chick embryo yolk sac

Abstract: Formation of the yolk sac vascular system and its connection to the embryonic circulation is crucial for embryo survival in both mammals and birds. Most mice with mutations in genes involved in vascular development die because of a failure to establish this circulatory loop. Surprisingly,formation of yolk sac arteries and veins has not been well described in the recent literature. Using time-lapse video-microscopy, we have studied arterial-venous differentiation in the yolk sac of chick embryos. Immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
339
1
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 435 publications
(363 citation statements)
references
References 48 publications
7
339
1
10
Order By: Relevance
“…6A,B) or section (data not shown) examination. A similar observation, in addition to the lack of prominent apoptosis during this period, has also been reported previously (le Noble et al, 2004). This suggested that these definitive erythropoietic cells are derived either from blood-borne hematopoietic cells or from pre-existing vascular cells.…”
Section: Pre-existing Vascular Endothelium Is a Likely Source For Defsupporting
confidence: 89%
See 2 more Smart Citations
“…6A,B) or section (data not shown) examination. A similar observation, in addition to the lack of prominent apoptosis during this period, has also been reported previously (le Noble et al, 2004). This suggested that these definitive erythropoietic cells are derived either from blood-borne hematopoietic cells or from pre-existing vascular cells.…”
Section: Pre-existing Vascular Endothelium Is a Likely Source For Defsupporting
confidence: 89%
“…The first phase, in which yolk sac vascular plexus is remodeled to form well-arborized arterial and venous trees, takes place between E2 and E3, soon after the initiation of embryonic circulation. This phase of vascular remodeling has been reported to be controlled by hemodynamics in the yolk sac (le Noble et al, 2004). Our observations suggest that yolk sac definitive erythropoiesis does not coincide with, although it may be a consequence of, this remodeling.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…L'apparente homogénéité des vaisseaux primitifs avant leur remodelage pouvait suggérer une implication importante des forces hémodynamiques dans ce remodelage [3]. Nous avons récemment réalisé une étude détaillée du remodelage du plexus vasculaire primitif en artères et en veines chez l'embryon de poulet [4]. Dans ce modèle, on peut visualiser directement, in vivo, la circulation sanguine et le sens du flux par vidéo-microscopie.…”
Section: Le Remodelage Artères/veinesunclassified
“…Ce processus est contrôlé par le flux sanguin qui croît dans les tubes vitellins majeurs, ce qui entraîne une diminution du diamètre des tubes annexes suivie de leur obturation. Ces vaisseaux déconnec-tés sont, par la suite, réutilisés pour façonner le réseau veineux secondaire qui se met en place dorsalement et parallèlement au réseau artériel [4]. Pour se reconnecter à la circulation veineuse, les branches annexes bourgeonnent dorsalement et perpendiculairement aux artères.…”
Section: Le Remodelage Artères/veinesunclassified